‘Behind the Church Door Stands the Devil’: Derek Walcott, the Caribbean Church, and the Island of Saint Lucia - Jefferson, Ben Thomas (Journal for the Study of Religion, Nature and Culture, 2013)
Steadfastly aware of a complex history of colonization and indoctrination, Nobel Prize winning poet Derek Walcott had an uneasy relationship with the majority Catholic Church in Saint Lucia for much of his life and was especially wary of any moves to delineate between the sacred site of the church and the ‘profane’ realm of the Caribbean natural world. A turning point in this was the creation of a fresco at the Holy Family RC Church in Jacmel, Saint Lucia, which, through its depiction of the natural world, helped Walcott to reconcile and heal some of his differences with Europeanized Catholic ideologies through the removal of the church’s monopoly over sacred space. Finally in Omeros (1990), Walcott continued his discourse on the tensions between churches and their surrounding landscapes and, without fully resolving these tensions, reaf?rmed the natural world as the most appropriate sacred space in the Caribbean.